2010
DOI: 10.1242/jeb.045955
|View full text |Cite
|
Sign up to set email alerts
|

The consequences of reversible gill remodelling on ammonia excretion in goldfish (Carassius auratus)

Abstract: SUMMARYGoldfish acclimated to cold water (e.g. 7°C) experience a marked reduction in functional lamellar surface area owing to the proliferation of an interlamellar cell mass (ILCM), a phenomenon termed gill remodelling. The goal of the present study was to assess the consequences of the reduced functional surface area on the capacity of goldfish to excrete ammonia. Despite the expected impact of ambient temperature on functional surface area, fish acclimated to 7°C and 25°C exhibited similar rates of ammonia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Finally, as mRNA is only itself an indirect measurement of transporter expression, protein expression analysis (through immunocytochemical studies; e.g. Perry et al 2010) would reveal if the increase in mRNA expression relates to an increase in transporter number and not simply an increase in transporter turnover rate.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, as mRNA is only itself an indirect measurement of transporter expression, protein expression analysis (through immunocytochemical studies; e.g. Perry et al 2010) would reveal if the increase in mRNA expression relates to an increase in transporter number and not simply an increase in transporter turnover rate.…”
Section: Discussionmentioning
confidence: 99%
“…Gill re-modelling has been widely suggested as an adaptive strategy to cope with stressful environments. An exposure test of goldfish, Carassius auratus (highly ammonia-resistant cyprinid), suggested that the posterior sides of the lamellae may play a role in the inter-lamellar cell mass´capacity to hinder branchial ammonia excretion (Perry et al, 2010b;Smith et al, 2012). Thickening of filaments and lamellae in the form of enlargement of inter-lamellar cell mass as observed in our study has also been found for common carp, Cyprinus carpio (a less ammonia-sensitive cyprinid), clearly for goldfish, and although less clear and very slowly (Sinha et al, 2014) even for rainbow trout, Oncorhynchus mykiss (highly ammonia sensitive).…”
Section: Toxicity Of Ammonia To Fish In Natural Environmentsmentioning
confidence: 99%
“…The possibility that increases in Rhesus (Rh) glycoprotein expression in the gills promoted ammonia excretion at HEA in these fish is another intriguing possibility given the role of these proteins in teleost ammonia excretion (for reviews, see Weihrauch et al, 2009;Wright and Wood, 2009). The Rh glycoproteins Rhcgb and Rhcg are not only found on the lamella of goldfish (Perry et al, 2010) but also on the inter-lamellar cell masses (ILCM) that are formed between lamellae of cold-acclimated goldfish (Sollid et al, 2005).…”
Section: Effects Of Hea On Muscle Nitrogen Stores and Urea Excretion mentioning
confidence: 99%